Discussions about the first years of Lourdes de la Rosa Onuchic's work in Rio Claro - Toillier, Jean Sebastian [UNESP] (FapUNIFESP (SciELO), 2025)
This article focuses on Lourdes de la Rosa Onuchic’s time, from 1959 to 1966, as a teacher at the former Faculty of Philosophy, Sciences and Letters of the Isolated Institute of Higher Education in Rio Claro, São Paulo. Thus, first of all, we’ll briefly highlight her academic degree and professional life before she started working as a teacher on the Mathematics degree course and the Pedagogy course at the institute, in Rio Claro. Next, we address the theoretical and methodological aspects that seek to relate biographical writing to the use of oral history. Afterwards, notes are taken on our character’s arrival in Rio Claro and about how gender relations influenced this period of her life. We also discuss her time as a scholarship student in the United States and how her studies on modern mathematics reverberated when she returned to Brazil. Finally, we briefly point out the following years of Lourdes’s academic and professional trajectory as well as how the story of a life can be important for learning more about Mathematics Education, Mathematics as a professional field and how gender relations permeate the university environment and the entire society.
Discussões sobre os primeiros anos de trabalho de Lourdes de la Rosa Onuchic em Rio Claro
Keywords: Biographical writing; Gender; New Math; Oral History